2012
DOI: 10.2215/cjn.00920112
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Nephrology

Abstract: SummaryThis review highlights factors of importance for the clinical care of pregnant women with pregestational diabetes and microalbuminuria or diabetic nephropathy with particular focus on the role of intensive antihypertensive treatment during pregnancy. Most information in the literature comes from women with type 1 diabetes and diabetic nephropathy, but this is probably also valid for women with type 2 diabetes. Careful counseling of women with diabetic nephropathy before pregnancy with estimation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 66 publications
0
22
1
4
Order By: Relevance
“…A review of the literature of the last decade underlines not only the persistence of a higher risk for adverse pregnancy-related outcomes compared to non-diabetic pregnancies, but also raises new questions about an increase in fetal malformations in patients with diabetic nephropathy [12][13][14][15][16][17][18][19][20]. Most of the studies published so far on diabetic nephropathy during pregnancy were designed in a diabetology setting, ideal for the identification and follow-up of early diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature of the last decade underlines not only the persistence of a higher risk for adverse pregnancy-related outcomes compared to non-diabetic pregnancies, but also raises new questions about an increase in fetal malformations in patients with diabetic nephropathy [12][13][14][15][16][17][18][19][20]. Most of the studies published so far on diabetic nephropathy during pregnancy were designed in a diabetology setting, ideal for the identification and follow-up of early diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…The chance of women with diabetic nephropathy having a 'take home baby' is thus very high. Other studies have demonstrated that the risk of pregnancy-induced deterioration of diabetic nephropathy is low if women enter the pregnancy with a serum creatinine level <200 μmol/l [3], and only one woman received dialysis treatment in the present cohort of pregnant women [1].…”
mentioning
confidence: 60%
“…Patients presenting Patients should be advised that advanced kidney disease significantly increases the risk of complications during pregnancy, including preeclampsia and premature birth. Moreover, the risk correlates with the stage of kidney disease; there are also studies describing the progression of kidney disease during pregnancy [7][8][9].…”
Section: Evaluation Of Kidney Functionmentioning
confidence: 99%